THE EFFECT OF USING BOARD GAME ON THE SECOND YEAR STUDENTS’ SPEAKING ABILITY AT SMP IT AL- IHSAN BOARDING SCHOOL - Fithri, Sathia Juliana; ', Marzuki; ', Afrianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study was aimed at investigating the effect of using Board Game on the second year students’ speaking ability at SMP IT Al-Ihsan Boarding School, Siak Hulu, Kampar. This study was an experimental quantitative research.The population of this research was all the second year students at SMP IT AL-Ihsan Boarding School. This research was conducted by applying Board Game in teaching speaking to the experimental group (Qodisiyah Class) selected by employing cluster random sampling method. There were 17 students in experimental group who had a pre-test, then they were taught by using Board Game, and they finally had a post-test to see the increase of their scores. After all data were collected, the researcher calculated them by using t-Test method in Ms. Excel 2010. With the t-Test score was 4.41, it can be concluded that there was a significant effect of using Board Game on the second year students’ speaking ability at SMP IT Al-Ihsan Boarding School that could be seen from the improvement of students’ scores in post-test.Key Words: Junior High School Students, Speaking Ability, Board Game